Reflective Ability Rubric and User Guide - Patricia O'Sullivan; Louise Aronson; Eva Chittenden; Brian Niehaus; Lee Learman (Association of American Medical Colleges, 2010)
Abstract This resource is a rubric for scoring reflective ability. It includes a user guide, which provides development and psychometric details, along with materials to be used in rater training. Our objective was to develop and provide a rubric that could be used by others to describe the learner's level of reflective ability as determined from a written essay stimulated by a prompt. Prompts vary, but they generally provide a topic or focus for the reflection, such as "Reflect on a patient who taught you the most about treating a patient with dignity and respect" or "Reflect on a recent clinical or other professional situation where you made a mistake or didn't have the necessary knowledge or skills." The effectiveness of the rubric has been demonstrated in its ability to distinguish between junior and senior residents. Likewise, the rubric's effectiveness has also been demonstrated in its ability to associate with related ratings and not with irrelevant ratings. Additionally, the scores from the rubric increased with specific training in reflection.